Analisis Kemampuan Komunikasi Matematis Siswa SMK Di Kota Cimahi Pada Materi Program Linear - Adi Rustandi; Rendi Firmansyah (Journal on Education, 2019)
Mathematics is the ability of students to convey mathematical messages or ideas, which are symbols, mathematical formulas or graphs, as well as complete mathematics. The importance of mathematical communication is to help students sharpen ways to improve and improve both social problems or solve mathematical problems. The research method used is descriptive qualitative. The sample in this study were 3 students of class XI with high, medium, and low abilities in SMK PUSDIKHUBAD Cimahi. There were five communication questions that were given that were agreed with each student. Then the results obtained are the results of mathematical communication of vocational students in Cimahi City based on written tests and the results of interviews with students who are still lacking.